2020
DOI: 10.1111/iwj.13452
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral reduction mammaplasty with pulsed electron avalanche knife PlasmaBlade™ and conventional electrosurgical surgery: A retrospective, randomised controlled clinical trial

Abstract: Wound‐healing disorders are common complications in bilateral reduction mammaplasty. Traditional electrosurgical devices generate large amounts of thermal energy, often causing extensive thermal‐related collateral tissue damage. This study aimed to retrospectively analyse the operative performance of a novel low‐thermal plasma dissection device (pulsed electron avalanche knife—PEAK PlasmaBlade™) compared with traditional electrosurgery. Twenty patients with breast hypertrophy were randomly treated with PEAK Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…Our analysis yielded the significant (p* = 0.0324) finding of a higher cumulative wound fluid quantity in the monopolar electrocautery group (351.11 ± 185.96 ml) compared to the PEAK PlasmaBlade group (279.38 ± 183.38 ml). While previous research on this topic has provided inconclusive data, some studies support our finding by reporting lower total drain output following the use of the PEAK PlasmaBlade [11,[17][18][19][20]22], whereas other authors found no difference between the two dissection devices [21,25,26]. It's worth noting that, to the best of our knowledge, no prior study has reported an increase in seroma rates after utilizing the PEAK Plasma Blade.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our analysis yielded the significant (p* = 0.0324) finding of a higher cumulative wound fluid quantity in the monopolar electrocautery group (351.11 ± 185.96 ml) compared to the PEAK PlasmaBlade group (279.38 ± 183.38 ml). While previous research on this topic has provided inconclusive data, some studies support our finding by reporting lower total drain output following the use of the PEAK PlasmaBlade [11,[17][18][19][20]22], whereas other authors found no difference between the two dissection devices [21,25,26]. It's worth noting that, to the best of our knowledge, no prior study has reported an increase in seroma rates after utilizing the PEAK Plasma Blade.…”
Section: Discussionsupporting
confidence: 68%
“…Studies assessing outcomes in extensive wound areas, like those involved in autologous breast reconstruction using the abdominal donor site, have often been limited by small sample sizes [11,[17][18][19][20][21][22]25,26]. While more extensive investigations have been undertaken in distinct surgical contexts, such as tonsillectomy [27-29] and surgical implant replacement [30], these findings may not be directly applicable to the specific circumstances of autologous breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing outcomes in extensive wound areas, like those involved in autologous breast reconstruction using the abdominal donor site, have often been limited by small sample sizes [11,[17][18][19][20][21][22]25,26]. While more extensive investigations have been undertaken in distinct surgical contexts, such as tonsillectomy [27][28][29] and surgical implant replacement [30], these findings may not be directly applicable to the specific circumstances of autologous breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has generated conflicting and inconclusive findings regarding whether the choice of the surgical dissection device significantly impacts clinical outcomes. While some studies suggest benefits associated with using the PPB, such as reduced seroma rates and shorter drain dwelling times, these studies have limitations, notably small sample sizes and none have evaluated patient-specific risk factors in this context [11,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although more shreds of evidence are needed, it has several advantages like shorter wound-healing time, pain-free swallowing, minimal collateral tissue damage, etc. [ 106 , 107 ]. Along with that, a recent clinical case study demonstrated the advantages of a mono-polar plasma knife in unilateral breast-conserving surgery over the traditional mastectomy.…”
Section: Introduction Low-temperature Plasma On Medicinementioning
confidence: 99%